2013
DOI: 10.1017/s0033291713002791
|View full text |Cite
|
Sign up to set email alerts
|

Group therapy for people with bulimia nervosa: systematic review and meta-analysis

Abstract: Conclusions could only be reached for CBT. Low-quality evidence suggests that group CBT is effective compared with no treatment, but there was insufficient or very limited evidence about how group and individual CBT compared. The risk of bias and imprecise estimates of effect invite further research to refine and increase confidence in these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…While MFT demonstrated potential in the treatment of adolescents living with AN (Hollesen et al, 2013), CBT was found to be more beneficial for those living with BN (Lazaro et al, 2011). This is consistent with the findings for BN among the adult population (Brownley et al, 2007;Polnay et al, 2013;Zimpfer, 1990).…”
Section: Interventionssupporting
confidence: 81%
See 1 more Smart Citation
“…While MFT demonstrated potential in the treatment of adolescents living with AN (Hollesen et al, 2013), CBT was found to be more beneficial for those living with BN (Lazaro et al, 2011). This is consistent with the findings for BN among the adult population (Brownley et al, 2007;Polnay et al, 2013;Zimpfer, 1990).…”
Section: Interventionssupporting
confidence: 81%
“…There exists a body of literature demonstrating the effectiveness of group cognitive behavioral therapy (CBT) in the treatment of adults living with BN (Brownley et al, 2007;Polnay et al, 2013;Zimpfer, 1990). Dialectical behavior therapy (DBT) has shown promise in the treatment of adults living with both BN and BED (Chen & Safer, 2010;Erb, Farmer, & Mehlenbeck, 2013;Safer, 550618S GOXXX10.1177 1 University of Melbourne, Australia Telch, & Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous RCTs of individual CBT have had greater success in achieving abstinence, with 38–47% of patients reporting abstinence by the end of 20-week treatment [17, 29, 30]. Our findings may represent an improvement over previous RCTs of group CBT, which reported 0–16% of participants abstinent by post-treatment, and only 10% at 6-month follow up [3133]. Subsequent papers will examine treatment effectiveness by taking into account other individual characteristics associated with outcome (i.e., moderators) and explore potential adverse effects of psychotherapy [34, 35].…”
Section: Discussionmentioning
confidence: 41%
“…We found five past meta-analyses that compared the effects of group and individual psychotherapy for EDs, however, the majority of these are out of date, targeted only bulimia nervosa (BN), and reported conflicting results (Erford et al, 2013;Fettes & Peters, 1992;Hartmann, Herzog, & Drinkmann, 1992;Polnay et al, 2014;Thompson-Brenner, Glass, & Westen, 2003). We found five past meta-analyses that compared the effects of group and individual psychotherapy for EDs, however, the majority of these are out of date, targeted only bulimia nervosa (BN), and reported conflicting results (Erford et al, 2013;Fettes & Peters, 1992;Hartmann, Herzog, & Drinkmann, 1992;Polnay et al, 2014;Thompson-Brenner, Glass, & Westen, 2003).…”
Section: Group Psychotherapy For Eating Disorders: Findings Of Pastmentioning
confidence: 99%
“…The authors suggested further research be conducted to refine and improve the quality of their findings (Polnay et al, 2014). Results of this meta-analysis are limited due to the small number of primary studies that were included (N 5 10).…”
Section: Group Psychotherapy For Eating Disorders: Findings Of Pastmentioning
confidence: 99%